(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2010)
This article deals with the analysis of the Ukrainian artistic discourse which includes ethnic stereotypes and prejudices; it describes the mechanism of speech realization of information through the experience of interethnic contacts; the article characterizes the speech strategies and models that give the opportunity to reach both discursive and social aims effectively; the cognitive model of the expression of ethnic estimations is interpreted.